Analisis Pengaruh Teknologi IoT terhadap Optimalisasi Efisiensi Smart City - Muhammad Reffy Adrian (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2025)
Internet of Things (IoT) technology plays an important role in Smart City development by increasing efficiency in the transportation, energy, waste management and air quality sectors. IoT enables dynamic regulation of traffic flow, more efficient energy management, and real-time monitoring of waste and air quality. However, challenges such as inadequate infrastructure, data security issues, and limited human resources need to be overcome to maximize IoT adoption. By improving infrastructure, interoperability standards and data security policies, the potential of IoT in Smart Cities can be further optimized.